Peran Efikasi Diri Akademis dan Kepuasan Hidup terhadap Kecenderungan Stres pada Mahasiswa - Permata Sari, Diana; Dewi, Luh Bulan Nisita; Larasati, Chatarina Lintang (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2025)
This quantitative study aims to look at intrapersonal factors, namely academic self-efficacy and life satisfaction, that can predict stress in final year college students. The research hypotheses are that academic self-efficacy and life satisfaction are negatively and significantly associated with stress among final year college students. Participants were 232 students who were in the sixth- and eighth-semester, with an age range of 20–25 years (Mage = 21.07, SD = 0.892). Academic self-efficacy was measured using the Academic Self-Efficacy Scale (TASES), life satisfaction was measured using the Satisfaction with Life Scale (SWLS), and stress was measured using the Depression, Anxiety, and Stress Scale-21 (DASS-21). The data analysis method used is multiple regression analysis. The results of multiple regression analysis show that academic self-efficacy and life satisfaction jointly have a significant negative effect on stress tendencies among the participants, F(2, 229) = 60.403, p .001, R² = .345. Based on these results, it can be concluded that academic self-efficacy and life satisfaction have a relationship and are able to negatively and significantly predict stress in sixth- and eighth-semester college students. These findings highlight the importance of fostering academic self-efficacy and enhancing life satisfaction among students to mitigate stress levels. Future interventions could focus on developing strategies that promote these psychological factors to improve overall well-being in academic settings.